House ownership and land use of «meshchanie» on the territory of Belarus (1860s – beginning of XX century) - Tserashkova, Kseniya S. (Journal of the Belarusian State University. History, 2018)
On the basis of legislative and office administration sources peculiarities of meshchanie house ownership and use of land on the territory of Belarusian-Lithuanian provinces from 1860s until the beginning of the XX century are analyzed. Specificity of governmental policy regarding house ownership and land use of meshchanie are defined. Structure of meshchanie real estate and its price is found, trends for increase of real estate role as a tax object and budget revenue source is proved. System of rented land use is studied as well as legislation and practice of renting of urban land parts into temporary use by meshchanie. A conclusion is made that the limits in real estate use in cities and towns was defined by state law of property for the lands, where living and economic buildings of meshchanie were built, and a short term of land use.